The Prevalence of Medical Student Mistreatment and Its Association with Burnout - Cook, Alyssa F. (Acad Med, 2014)
PURPOSE: Medical student mistreatment has been recognized for decades and is known to adversely impact students both personally and professionally. Similarly, burnout has been shown to negatively impact students. This study assesses the prevalence of student mistreatment across multiple medical schools and characterizes the association between mistreatment and burnout. METHOD: In 2011, the authors surveyed a nationally representative sample of third-year medical students. Students reported the frequency of mistreatment by attending faculty and residents since the beginning of their clinical rotations. Burnout was measured using a validated two-item version of the Maslach Burnout Inventory. RESULTS: Of 919 eligible students from 24 different medical schools, 564 (61%) completed the survey. The majority reported at least one incident of mistreatment by faculty (64% [361/562]) and by residents (75.5% [426/562]). Notable minorities experienced recurrent mistreatment, defined as mistreatment categorized as “several” or “numerous” times by student self-report (10.7% [59/562] by faculty and 12.6% [71/562] by residents). Recurrent mistreatment was associated with high burnout (57.4% vs. 31.5%; p<0.01 for recurrent mistreatment by faculty; 49.1% vs. 32.1%; p<0.01 for recurrent mistreatment by residents). CONCLUSIONS: Medical student mistreatment remains prevalent. Recurrent mistreatment by faculty and residents is associated with medical student burnout. Although further investigation is needed to assess causality, these data provide additional impetus for medical schools to address student mistreatment to mitigate its adverse consequences on their personal and professional well-being.